Test-Retest of the Spot Vision Screener among Children with Ophthalmological Diseases including Strabismus - Mika Ichimura; Satoshi Ueki; Takeo Fukuchi (Journal of Ophthalmology)
Background. The spot vision screener (SVS) has been widely used for eye health examinations of infants and young children. The purpose of this study was to evaluate the reproducibility of two SVS measurements in children with ophthalmological diseases. Methods. 29 patients aged 15 years or younger who visited our hospital for refraction examinations with SVS before and at least 60 minutes after administration of 2 drops of 1% cyclopentolate ophthalmic solution (before and after cycloplegia) were included in this study. Two SVS measurements were made before and after cycloplegia, respectively. Intraclass correlation coefficients (ICCs) and Bland–Altman analysis for spherical, spherical equivalent (SE), cylindrical, J0, and J45 values before and after cycloplegia were analyzed. Results. The mean age ± standard deviation (SD) of the 29 patients was 7.6 ± 2.4 years. There were 11 males and 18 females. The mean spherical values based on the SVS before and after cycloplegia were 0.42 ± 1.67 diopter (D), and 1.47 ± 2.23 D for the first measurement and 0.60 ± 1.74 D, and 1.42 ± 2.27 D for the second measurement, respectively. The mean cylindrical values based on SVS before and after cycloplegia were −1.45 ± 0.96 D and −1.65 ± 0.89 D for the first measurement and −1.58 ± 1.13 D and −1.66 ± 0.91 D for the second measurement, respectively. The ICCs for the first and second spherical, SE, cylindrical, J0, and J45 values before cycloplegia were 0.95, 0.98, 0.83, 0.86, and 0.86, respectively. The ICCs for the first and second spherical, SE, cylindrical, J0, and J45 values after cycloplegia were 0.99, 0.99, 0,87, 0.73, and 0.80, respectively. The Bland–Altman analysis of the first and second spherical and SE values before cycloplegia showed fan-shaped variation as hyperopia increased. Conclusions. Two consecutive SVS refraction measurements have a high degree of reproducibility for spherical and SE values but a low degree for cylindrical, J0, and J45 values. From these results, multiple measurements are required to obtain reliable results for cylindrical values.